Neuropsychological Deficits Are Not Predictive of Deficient Emotional Self-Regulation in Adults With ADHD. (December 2015) - Surman, Craig B. H.; Biederman, Joseph; Spencer, Thomas; Miller, Carolyn A.; Petty, Carter R.; Faraone, Stephen V.
Objective: To investigate whether neuropsychological deficits account for the association between deficient emotional self-regulation (DESR) and ADHD.Method: DESR was identified in adults with and without ADHD who reported extreme frequency of items from the Barkley Current Behavior Scale (>95th percentile of control participants). A neuropsychological battery and structured diagnostic interview were administered to 113 adults with ADHD and DESR, 93 adults with ADHD without DESR, and 119 participants without ADHD or DESR.Results: Relative to adults with ADHD without DESR, adults with ADHD and DESR demonstrated lower scores on Wechsler Adult Intelligence Scale (WAIS) arithmetic but no other significant differences in neuropsychological performance. Relative to adults without ADHD, both ADHD groups demonstrated lower scores across several measures of executive function.Conclusion: Our findings do not support the hypothesis that neuropsychological deficits are linked to DESR in adults with ADHD. This finding is consistent with the hypothesis that DESR could be a manifestation of ADHD, but further study of alternate hypotheses is necessary to support this conclusion.